A Comparative Study on Lignite Coal Drying by Different Methods. Issue 2 (1st February 2020) - Rahman, Moshfiqur; Kurian, Vinoj; Pudasainee, Deepak; Gupta, Rajender
ABSTRACT: Abundance of low-rank coal (LRC) and increasing demand for energy provides motivation for upgrading LRC in terms of their high moisture content. Canadian lignite coal (425–1000 µm) was dried at different temperatures using different methods, namely hydrothermal treatment (HT), vacuum drying and hot air drying. These processes resulted in significant reduction (up to 9.65%) in moisture from as-received lignite coal (34%), especially at higher temperatures (300 and 325°C) using HT for 30 minutes. Vacuum drying (70°C) over the period of 7 hours and hot air drying (70°C) for 110 minutes liberated almost the same amount of moisture from the raw coal. Several investigations were conducted on these samples and chars derived from these in conditions similar to a boiler to understand the impact of drying methods. Char samples were prepared by pyrolyzing at 1200°C under inert atmosphere (N2 ) in a drop tube furnace (DTF). The morphological changes of these char samples were investigated by scanning electron microscopy analysis to see the physiochemical changes that occurred during different treatment processes. Raw and treated coal samples were also analyzed by several analytical techniques including Fourier transform infrared spectroscopy and thermogravimetric analysis (TGA). The present paper also describes the effectiveness of the different processes for upgrading the LRC and how it transforms LRC to a value-added coal that is easily transportable and environmental friendly source of energy.